2021
DOI: 10.1111/apt.16533
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: duodenogastroesophageal (biliary) reflux prevalence, symptoms, oesophageal lesions and treatment

Abstract: Summary Background The prevalence of duodenogastroesophageal reflux (DGER) and its effect on symptoms and oesophageal lesions in gastroesophageal reflux disease (GERD) is unclear. Aims To conduct a systematic review to determine the prevalence of DGER among patients with GERD, the effect of DGER on symptoms and oesophageal lesions, and the treatment of DGER. Methods We searched Pubmed and MEDLINE for full text, English language articles until October 2020 that evaluated DGER prevalence among patients with GERD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
7
0
1
Order By: Relevance
“…The results of this study demonstrate that the daily consumption of dairy products and a preference for fried food are independent risk factors for DGR. Previous studies have confirmed that slight levels of DGR may be physiologically present in the stomach after feeding and fasting (13). Bile is considered a major duodenal component.…”
Section: Discussionmentioning
confidence: 84%
“…The results of this study demonstrate that the daily consumption of dairy products and a preference for fried food are independent risk factors for DGR. Previous studies have confirmed that slight levels of DGR may be physiologically present in the stomach after feeding and fasting (13). Bile is considered a major duodenal component.…”
Section: Discussionmentioning
confidence: 84%
“…According to the data of recent epidemiological studies, there has been a decrease in the proportion of Helicobacter pylori-associated gastritis with an increase in the contribution of other etiological factors. Thus, the prevalence of gastritis associated with bile reflux ranges from 17% to 24%, reaching 62% in a cohort of patients with risk factors for duodenogastric reflux [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…6 Bile reflux gastritis occurs when the contents of the duodenum, which can disrupt the gastric mucosal barrier with various factors, leak back into the stomach and cause inflammation. 7, 8 The majority of cases involve asymptomatic chronic inflammation. Upper gastrointestinal endoscopy is used to differentiate between bile reflux gastritis and H. pylori gastritis.…”
Section: Introductionmentioning
confidence: 99%